From Nuremberg to the Hague: The Novelties of Establishing the Permanent International Criminal Court - Škulić, Milan (The ICC at 25: Lessons Learnt, 2025)
The chapter outlines the basic features of the development of international criminal law and international criminal justice, with a special emphasis on the establishment of the permanent International Criminal Court, which the author has treated as a new beginning rather than the end of the development of international criminal justice.The author has also provided an overview of the history of international criminal justice, closely associated with the history of civilisation, military history for the most part, covering the fundamental stages thereof – its “juvenility”, so to speak, the landmark Nuremberg Trials and the other tribunals since World War II.The main point is that when it comes to the future of the International Criminal Court, one should be neither an optimist nor a pessimist, and for what lies ahead of the first permanent form of international criminal justice, the old truth holds that a glass halfway filled with water may be seen as either half-full or half-empty. Keywords: International Criminal Law, International Criminal Justice, Nuremberg, IMT, Permanent International Criminal Court, ICC